Smart City Kids Lab: Creative Computing in Primary School - Gomes, Cristina Azevedo (2022)
In recent years there is a growing interest in including programming activities in education, emphasizing the importance of children developing computer thinking since early ages. Block-based programming environments scaffold children to explore and learn programming in an easier way. In this paper we present a project supported by a theoretical framework that mobilizes constructionism, the maker movement, tinkering, and project-based learning, and a practical framework based on workshops with primary teachers. Primary school children developed computational thinking and creative computing skills, while they design and present ideas to turn their city a smart city. Results show the quality of the products developed using programming and robots and the impact that this approach can have in authentic learning.